Development of Independent Learning Activity Unit of Digital Based on Android to Improve Student Learning Outcomes - Maimun, Maimun; Jannah, Miftahul (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This study aims to develop ILAU Digital Based on Android in improving student learning outcomes in Islamic religious education materials in Madrasah Aliah. This type of research is included in Research and Development (R&D) with development stages such as define, design, develop and disseminate. Data collection techniques used in this study are expert validation, response questionnaires, and written tests. Validity data analysis using Aiken’s V and Percentage of Agreement. Analysis of increased learning outcomes using the N-Gain test. Taking data on learning outcomes based on the Nonequivalent Control Group design so that there are experimental and control classes. The results of expert validator assessment show that the research instrument and products developed are included in the very valid category. Students and teachers give very good responses to the use of products. Ilau Digital based on Android is practically used in learning. Meanwhile, the results of the effectiveness test show that Android -based digital ilau products can improve student learning outcomes and affect student learning outcomes. The increase that occurred after the use of the product was 82% and included in the effective category. The conclusion of this study is that the development of Android -based digital ilau can improve student learning outcomes.